2020
DOI: 10.1038/s41467-020-18874-y
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the deltaretroviral intasome in complex with the PP2A regulatory subunit B56γ

Abstract: Human T-cell lymphotropic virus type 1 (HTLV-1) is a deltaretrovirus and the most oncogenic pathogen. Many of the ~20 million HTLV-1 infected people will develop severe leukaemia or an ALS-like motor disease, unless a therapy becomes available. A key step in the establishment of infection is the integration of viral genetic material into the host genome, catalysed by the retroviral integrase (IN) enzyme. Here, we use X-ray crystallography and single-particle cryo-electron microscopy to determine the structure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 63 publications
(94 reference statements)
0
28
0
Order By: Relevance
“…We next wanted to understand the interactions between the CTD and the “tail” region of IN to promote the assembly of intasomes and to foster virus infectivity. CTDs play critical roles in stabilizing functional retrovirus intasome CICs 1 , 3 , 4 , 6 , 8 . The RSV IN “tail” region (defined as residues from Ile269 to Ala286; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next wanted to understand the interactions between the CTD and the “tail” region of IN to promote the assembly of intasomes and to foster virus infectivity. CTDs play critical roles in stabilizing functional retrovirus intasome CICs 1 , 3 , 4 , 6 , 8 . The RSV IN “tail” region (defined as residues from Ile269 to Ala286; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structures of different retroviral IN-DNA complexes capable of concerted integration show diverse organizations but possess significant mechanistic similarities. These structures, generally termed intasomes, contain multimers of IN subunits ranging from 4 for the simiispumavirus prototype foamy virus (PFV) 1,2 and delta-retroviruses human T-cell leukemia virus type 1 (HTLV-1) 3 and simian T-lymphotropic virus type 1 (STLV-1) 4 to 8 for alpha-retrovirus Rous sarcoma virus (RSV) 5 and betaretrovirus mouse mammary tumor virus (MMTV) 6 . For lentiviral intasomes, there are variable numbers of IN subunits ranging from 4 to 12 for HIV-1 and simian immunodeficiency virus (SIV) [7][8][9] and up to 16 subunits for maedi-visna virus (MVV) 10 .…”
mentioning
confidence: 99%
“…The X-ray crystallographic structure of deltaretroviral human lymphotropic virus type-1 (HTLV-1) IN residues 200-297, encompassing the LxxIxE SLiM, and B56 revealed a binding interface akin to that of BubR1 and RepoMan (Figures 2A, B), yet devoid of the phosphoserine-R188 interaction (Barski et al, 2020). Our understanding of the IN-PP2A binding was then largely expanded by two independent studies by Barski et al (2020) and Bhatt et al (2020) who have respectively reported structures of STLV-1 and HTLV-1 intasomes (IN:vDNA supramolecular intermediates) in complexes with B56. Both structures corroborated observations from the co-crystal complex but also identified a previously-unknown ligand binding site on B56.…”
Section: Emerging Role Of Viral Pp2a Targeting Via Lxxixe Motif Mimicrymentioning
confidence: 99%
“…Inhibition of PP2A activity prevents dephosphorylation of IKKγ which leads to activation of IKKγ-regulated genes and ultimately cell cycle arrest. HTLV-1 integrase (IN) associates with the B56 subunit to enhance infection and might play a role in integration site targeting ( Maertens, 2016 ; Barski et al., 2020 ; Bhatt et al., 2020 ). The relevance of cell senescence induced by both HIV-1 and HTLV-1 in the context of infection remains unknown.…”
Section: Pp2a Is Ubiquitously Targeted and Modulated By Virusesmentioning
confidence: 99%
“…In the past several years multiple retroviral intasomes have been visualized. These integration complexes include tetramers (PFV, HTLV-1), octamers (MMTV, RSV), and hexadecamer (maedi visna virus, MVV) ( Hare et al, 2010 ; Maertens et al, 2010 ; Ballandras-Colas et al, 2016 ; Yin et al, 2016 ; Ballandras-Colas et al, 2017 ; Barski et al, 2020 ; Bhatt et al, 2020 ). Several multimeric forms have been observed for simian immunodeficiency virus (SIV) and HIV-1 IN ( Passos et al, 2017 ; Cook et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%